Epidemiological characteristics of congenital heart diseases in Londrina, Paraná South Brazil - Guitti,José Carlos dos Santos (2000)
OBJECTIVE: To determine the prevalence and other epidemiological characteristics of congenital heart diseases. METHODS: A retrospective population based study of children who were born in Londrina, from January '89 to December '98 (80,262 live births). Diagnoses were confirmed through autopsy, surgery, catheterization, or echocardiography. RESULTS: A total of 441 patients was as certained what corresponds to a prevalence of 5.494:1,000 live births. Ventricular septal defect was the commonest lesion. A small number of transpositions of the great vessels and of left ventricular hypoplasia was observed. A high propation of ventricular septal defect (28.3%) and atrioventricular septal defects (8.1%) occurred. Fifty-one (11.35%) affected children had syndromic diseases and 52 (12.01%) children had nonsyndromic anomalies. CONCLUSION: The prevalence of congenital heart diseases in Londrina is in accordance with that of other regions of the globe. This prevalence also may reflect the reality in the southern region of Brazil, because population characteristics are very similar in the 3 southernmost Brazilian states.